Far from the madding crowd: Collective wisdom in prediction markets - Giulio Bottazzi; Daniele Giachini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
We investigate market selection and bet pricing in a simple Arrow security economy which we show is equivalent to the repeated prediction market models studied in the literature. We derive the condition for long run survival of more than one agent (the crowd) and quantify the information content of prevailing prices in the case of two fractional Kelly traders with heterogeneous beliefs. It turns out that, apart some non-generic situations, prices do not converge, neither almost surely nor on average, to true probabilities. Nor are they always nearer to the truth than the believes of all surviving agents. Moreover, we show that by adapting their beliefs to past prices, agents further decrease the agreement between market prices and true probabilities.
Keywords: C60; D53; G11; G12; 330; Prediction Markets; Bet Pricing; Wisdom of Crowds; Market Selection; Heterogeneous Beliefs; Fractional Kelly Rule